Molecular Diagnostic Techniques for Malaria Infection - A Review - Yangora, Y.M.; Usman, A.D. (UMYU Journal of Microbiology Research)
Malaria is the most threatening disease protozoal and a major health problem worldwide especially in developing countries. WHO recommended that for every case of suspected  malaria, diagnostic test must be done to confirm the disease. A more advanced Diagnostic Techniques were developed to overcome the problem of conventional microscopy. These techniques are known as Molecular diagnostic techniques, and they detect specific sequence in DNA, RNA and proteins to provide clinical information for human pathogens including malaria parasites. There are several techniques involve in molecular diagnostics, some are however discussed in this review. They include Polymerase Chain Reaction (PCR), Loop-mediated isothermal amplification (LAMP), Flow Cytometric technique (FCM), Nucleic acid based sequence amplification (NASBA), and Luminex xMax technology. Among these techniques; LAMP technique is the best techniques that can be deployed in the field settings (clinical and rural settings) because of its simplicity, reliability, stability, detection method as well as point-of- care and confirmatory ability. On the other hand, PCR-based technique is more suitable for research purposes because it can be used to identify drug resistance, follow-up therapeutic response, and detect asymptomatic malaria carriers who may be targeted for treatment. Hence, molecular diagnostic techniques are most innovative science and technical implementations that can be used to diagnose malaria infection and to overcome the limitations.